Deskripsi Penerapan Permainan Susun Warna Ceria untuk Menstimulasi Motorik Halus Anak Usia Dini - Sri Deyanti Paluwala; Fitriani Maun; Nabila Rahdani Mandjurungi; Pupung Puspa Ardini; Nadia Luawo; Salma Rahman; Siti Maryam Pomalo (Jurnal Pendidikan Bahasa dan Anak Usia Dini, 2026)
Fine motor skills are an essential aspect of early childhood development, as they involve the ability to use small muscles, particularly those of the fingers and wrists. These skills are required for various activities, such as grasping, transferring objects, arranging items, drawing, and writing. This study aims to describe the "Cheerful Color Stacking" game as a medium for stimulating fine motor skills in early childhood. This study employed a descriptive qualitative approach. Data were collected through observation, documentation, and field notes during the implementation of the game. The "Cheerful Color Stacking" game involved children arranging colored blocks or objects according to examples, patterns, or simple instructions provided by the teacher. The findings indicate that this game effectively stimulates children's fine motor skills, particularly in grasping objects, transferring items, coordinating hand and eye movements, arranging objects accurately, and maintaining concentration throughout the activity. The children appeared more active, enthusiastic, and engaged in the learning process because the materials used were colorful, concrete, and easy to manipulate. Therefore, the "Cheerful Color Stacking" game can serve as an enjoyable alternative play activity for stimulating fine motor skills in early childhood.